Zooarchaeological and stable isotope evidence of Sámi reindeer offerings - Salmi, Anna-Kaisa; Fjellström, Markus; Äikäs, Tiina; Spangen, Marte; Nunez, Milton; Lidén, Kerstin (Journal of Archaeological Science: Reports, 2019)
This paper presents new osteometric and stable isotope evidence of Sámi reindeer offerings. Previous archaeological studies have shown that reindeer domestication and intensification of reindeer herding transformed Sámi indigenous religion. However, because of the methodological challenges in the identification of wild and domesticated reindeer in the archaeological record, the exact nature of the relationship between people and offered reindeer has remained elusive. To address this problem, we analyze zooarchaeological and stable isotope data from thirteen Sámi offering sites situated in Finland and Sweden and dating to c. 1200–1700 CE. We employ zooarchaeological analysis of age, sex and size and explore the possibilities of these analyses to identify domestication and other characteristics of reindeer selected for offering. Analyses of stable isotopes of carbon, nitrogen and sulphur are utilized to identify human influence on reindeer feeding patterns and mobility. Our results show that many kinds of reindeer with different engagements with people were offered. The results confirm that people had different motives for giving offerings and that a simple dichotomy of wild/domesticated does not adequately reflect the range of relationships the Sámi had with reindeer.